Outcomes of Ceftaroline Fosamil q8h vs. q12h Dosing Frequency for High-Burden, Gram-positive Infections. (4th October 2017) - Rao, Sonia; Hayes, Jennifer; Kaye, Keith S; Chen, Jie; Johnson, Leonard
Abstract: Background: High-burden, Gram-positive (HBGP) infections such as bacteremia, endocarditis, hospital-acquired pneumonia/ventilator-associated pneumonia [HAP/VAP], and osteomyelitis are associated with substantial morbidity and mortality. CAPTURE, a retrospective, phase 4 study, describes clinical use of ceftaroline fosamil (CPT-F) in the United States. Clinical outcomes of patients with HBGP infections treated with CPT-F q8h (every 8 hours) vs. q12h (every 12 hours) are presented. Methods: Data including patient demographics, medical history, disease characteristics, antibiotic use, pathogens isolated, and clinical outcome were collected between September 2013 and February 2015 by review of randomly ordered patient charts from participating sites in the US. Clinical success was defined as discontinuation of CPT-F following clinical cure with no further need for antibiotic or clinical improvement with switch to another antibiotic. Results: In total, 541 patients with HBGP infections were treated with CPT-F (q8h, 22% [117/541]; q12h, 78% [424/541]). Demographics and baseline characteristics were well balanced; however, patients who received q8h dosing were more likely to have a diagnosis of bacteremia or endocarditis ( P < 0.001) and have infection with MRSA ( P < 0.001; Figure 1 ). Methicillin-resistant S.aureus was the most commonly isolated organism in the q8h (96/117; 82%) and q12h (255/424; 60%) groups. The mean (SD) duration of CPT-F therapy was 13.6 (10.8) and 8.4 (7.4) days in patients receiving q8h and q12h CPT-F, respectively. Monotherapy was used in 57% (311/541) of patients. The most commonly used concurrent antibiotics were vancomycin (12%; 64/542) and daptomycin (11%; 62/542). Clinical success rates of all patients with HBGP infections treated with CPT-F was >70% regardless of dosing frequency (Figure 2) . Overall clinical success in q8h vs. q12h treated individuals was 79% (92/117) and 83% (350/424), respectively. Discontinuation due to an adverse event occurred at a similar rate (q8h, 3% vs. q12h, 2%). Conclusion: High rates of clinical success were observed in patients treated with CPT-F q8h or q12h for HBGP infections, regardless of dose frequency despite more patients having had MRSA infection and/or bacteremia in the q8h cohort. Disclosures: S. Rao, Allergan plc: Employee, Salary; J. Hayes, Allergan plc: Employee, Salary; K. S. Kaye, Allergan plc: Consultant, Consulting fee; J. Chen, Allergan plc: Employee, Salary; L. Johnson, Allergan plc: Investigator, Research support